CNS Low-grade Diffusely Infiltrative Tumors With INI1 Deficiency, Possessing a High Propensity to Progress to Secondary INI1-deficient Rhabdoid Tumors. (November 2020) - Nobusawa, Sumihito; Nakata, Satoshi; Nakano, Yoshiko; Kawamura, Atsufumi; Yoshida, Makiko; Tamura, Akihiro; Hasegawa, Daiichiro; Kosaka, Yoshiyuki; Ito, Ichiro; Watanabe, Reiko; Oishi, Takuma; Hayashi, Nakamasa; et al.
Abstract : Atypical teratoid/rhabdoid tumors (AT/RTs) are highly malignant tumors of the central nervous system that predominantly occur in infants, and are characterized by the presence of rhabdoid cells and inactivation of INI1 or (rarely) BRG1. Most AT/RT are identified as primary tumors; however, rare AT/RT or INI1-deficient RTs arising from other primary tumors have been reported. Here, we report 3 cases of hitherto unclassifiable low-grade tumors with loss of INI1 nuclear expression, for which we propose the designation of central nervous system low-grade diffusely infiltrative tumors with INI1 deficiency (CNS LGDIT-INI1), 2 of which progressed to secondary RT. All 3 CNS LGDIT-INI1 exhibited a similar histology: diffusely distributed small tumor cells with round to oval or irregular nuclei and scant cytoplasm were admixed with degenerative neurons and large reactive astrocytes in an edematous, myxoid, or collagenous background. Mitotic figures were absent. Immunohistochemistry revealed that the tumor cells in all 3 CNS LGDIT-INI1 and 2 RT were negative for INI1. Genetically, total or partial homozygous deletions of the INI1 gene were detected in all CNS LGDIT-INI1 and RT excluding 1 CNS LGDIT-INI1 without sufficient DNA quality and quantity. Despite the loss of INI1 expression, these low-grade lesions were clearly distinguishable from AT/RT by their low proliferative activity, diffusely infiltrative growth pattern, and lack of rhabdoid cells and polyphenotypic immunoreactivity. In conclusion, CNS LGDIT-INI1 may represent a rare group of tumors that are clinically indolent but have a high propensity to progress to RT.